ATTENTION TO SLAVERY IN KASHKADARYA OASIS (TAMADDUN NURI JURNALI, 2024)
This article describes the development of karakulism in the oasis of Kashkadarya, issues related to it. In particular, the Kashkadarya Oasis describes issues related to the situation of blacksmithing in the period from 1925-1991, fodder, livestock feed policy, the impact of collectivization policies implemented in the region on blacksmithing, the implementation of blacksmithing plans.